Estimating the Value of Preserving the Doubs - Nikola Jovanoski (University of Neuchâtel, Institute of Economic Research (IRENE), 2015)
This analysis estimates the value that the inhabitants of the canton of Neuchâtel attach on the preservation of the Doubs. It is achieved with the use of the open-ended contingent valuation method. The results indicate that an inhabitant from this canton is, on average, willing-to-pay 55 CHF per year to preserve the Doubs, which translates to a value of up to 9.63m CHF that the inhabitants of this canton attach on the preservation of the Doubs. These estimates may be used as a guide by the relevant administrative and national authorities in the development of environmental policies.
Keywords: Q51; 330; contingent valuation method; open-ended elicitation method